Prophylactic drain management after pancreaticoduodenectomy without focusing on the drain fluid amylase level: A prospective validation study regarding criteria for early drain removal that do not include the drain fluid amylase level. (3rd June 2020) - Taniguchi, Koichi; Matsuyama, Ryusei; Yabushita, Yasuhiro; Homma, Yuki; Ota, Yohei; Mori, Ryutaro; Morioka, Daisuke; Endo, Itaru
Abstract: Background/Purpose: Early drain removal (EDR) based on drain fluid amylase level (DFA) after pancreaticoduodenectomy excluded 15%‐40% patients from EDR because of inappropriate DFA. Methods: Of 198 pancreatoduodenectomy cases, we used the first 105 cases as an exploration cohort to construct the optimal criteria for EDR on postoperative day (POD)4 that were applied to the subsequent 93 cases used as the validation cohort. After that, we examined another 142 patients to further assess the efficacy of the new EDR criteria. Results: Of the four independent predictors of clinically relevant postoperative pancreatic fistula (CR‐POPF) ([1] soft pancreas, [2] positive drain fluid culture on POD1, and [3] serum C‐reactive protein [CRP] ≥13 mg/dL on POD4) in the exploration cohort, EDR was applied to cases in the validation cohort meeting the [2] and/or [3], enabling 96% (89/93) applicability of EDR. Outcomes were improved in the validation cohort compared to the exploration cohort; CR‐POPF: 8.6% vs 25.7%, P  = .005; Dindo‐Clavien grade ≥  3 complications: 23.7% vs 41.9%, P  = .007; and median hospital stay (day): 21 vs 27, P  = .005. The subsequent 142 patients showed 92% (131/142) applicability of EDR and 5.6% (8/142) incidence of CR‐POPF. Conclusions: Our new criteria for EDR, without DFA, enabled ≥ 90% applicability of EDR and reduced CR‐POPF. Abstract : Taniguchi and colleagues conducted a retrospective study to determine the optimal criteria for early drain removal. Prophylactic drain management after pancreaticoduodenectomy using the new criteria yielded 90% or higher applicability of early drain removal and reduced the incidence of clinically relevant postoperative pancreatic fistula, resulting in reduced postoperative hospital stay.